Toxicity to RAW264.7 Macrophages of Silica Nanoparticles and the E551 Food Additive, in Combination with Genotoxic Agents - Fanny Dussert; Pierre-Adrien Arthaud; Marie-Edith Arnal; Bastien Dalzon; Anaëlle Torres; Thierry Douki; Nathalie Herlin; Thierry Rabilloud; Marie Carriere (Nanomaterials, 2020)
Synthetic amorphous silica (SAS) is used in a plethora of applications and included in many daily products to which humans are exposed via inhalation, ingestion, or skin contact. This poses the question of their potential toxicity, particularly towards macrophages, which show specific sensitivity to this material. SAS represents an ideal candidate for the adsorption of environmental contaminants due to its large surface area and could consequently modulate their toxicity. In this study, we assessed the toxicity towards macrophages and intestinal epithelial cells of three SAS particles, either isolated SiO2 nanoparticles (LS30) or SiO2 particles composed of agglomerated-aggregates of fused primary particles, either food-grade (E551) or non-food-grade (Fumed silica). These particles were applied to cells either alone or in combination with genotoxic co-contaminants, i.e., benzo[a]pyrene (B[a]P) and methane methylsulfonate (MMS). We show that macrophages are much more sensitive to these toxic agents than a non-differenciated co-culture of Caco-2 and HT29-MTX cells, used here as a model of intestinal epithelium. Co-exposure to SiO2 and MMS causes DNA damage in a synergistic way, which is not explained by the modulation of DNA repair protein mRNA expression. Together, this suggests that SiO2 particles could adsorb genotoxic agents on their surface and, consequently, increase their DNA damaging potential.